Striking a Balance: Optimal Tax Policy with Labor Market Duality - Gilbert Mbara; Joanna Tyrowicz; Ryszard Kokoszczynski (Institute of Labor Economics (IZA), 2020)
This paper develops a dynamic general equilibrium model where employers may avoid making social security contributions by offering some workers "secondary contracts". When calibrated using aggregate tax revenue data, the model delivers estimates of secondary "off the books" employment that are consistent with survey evidence for the EU14 and United States. We investigate the fiscal and welfare effects of varying the avoidable and unavoidable shares of labor income tax while keeping the total wedge constant, and find that increasing the employer component raises hours worked, output, and welfare. Partial labor tax evasion makes tax revenues more elastic, but full tax compliance need not be a welfare enhancing policy mix.
Keywords: H2; H26; H3; E13; E26; J81; 330; labor market duality; tax evasion; Laffer Curve